The long and winding road… - Francesca Helm (Journal of Virtual Exchange, 2018)
The long and winding road is a metaphor for a journey, often used to describe life journeys and the challenges encountered. The metaphor was used for the title of my keynote to refer both to the journey towards the current position of virtual exchange in education policy – but also the long road ahead. This paper aims to explore the emergence of virtual exchange in educational policy and how it has been adopted by non-profit organisations, educational institutions, and policy makers to address geo- and socio-political tensions. Though still a relatively new field, in recent years there have been some important developments in terms of policy statements and public investments in virtual exchange. The paper starts by looking at the current state-of-the-art in terms of virtual exchange in education policy and initiatives in Europe. Then, using an approach based on ‘episode studies’ from the policy literature, the paper explores the main virtual exchange schemes and initiatives that have drawn the attention of European policy makers. The paper closes by looking at some of the lessons we have learnt from research on the practice of virtual exchange, and how this can inform us as we face the long road ahead of us. The focus of this paper is on the European context not because I assume it to be the most important or influential, but rather because it is the one I know best, since it is the context in which I have been working.